Effects of institutional policies on employees with nonobvious disabilities - Anthony G. Stacey (African Journal of Disability, 2023)
Background: While legislation protects persons with disabilities against discrimination, decisions taken in line with institutional policies may still have a negative impact on the lived experience of those individuals.